2001
DOI: 10.1097/00006231-200107000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of atherosclerosis using a novel positron-sensitive probe and 18-fluorodeoxyglucose (FDG)

Abstract: Inflammation contributes to atherosclerotic plaque remodeling, enlargement and rupture. Non-invasive imaging of coronary artery inflammation could help target therapy to 'vulnerable' atheromata, but is limited because of small tissue mass and arterial motion. Local radiopharmaceutical imaging may overcome some of these limitations. We used a positron-sensitive fiberoptic probe, which can distinguish positron emissions from annihilation photons, to identify diseased from healthy endothelium in an atheroscleroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 17 publications
2
88
0
1
Order By: Relevance
“…Hypoxia is a prominent feature of the atherosclerotic milieu and associates strongly with the burden of macrophage infiltration and inflammation (41). Animal (42)(43)(44)(45)(46)(47)(48) and human (33,(49)(50)(51) studies have consistently demonstrated a correlation between 18 F-FDG uptake and the presence and density of macrophages in atherosclerosis. 18 F-FDG PET vascular imaging in humans was first described in 1999 in Takayasu's arteritis, before being investigated in other vasculitides (52)(53)(54).…”
Section: F-fdg Detection Of Vascular Inflammationmentioning
confidence: 99%
“…Hypoxia is a prominent feature of the atherosclerotic milieu and associates strongly with the burden of macrophage infiltration and inflammation (41). Animal (42)(43)(44)(45)(46)(47)(48) and human (33,(49)(50)(51) studies have consistently demonstrated a correlation between 18 F-FDG uptake and the presence and density of macrophages in atherosclerosis. 18 F-FDG PET vascular imaging in humans was first described in 1999 in Takayasu's arteritis, before being investigated in other vasculitides (52)(53)(54).…”
Section: F-fdg Detection Of Vascular Inflammationmentioning
confidence: 99%
“…Because the metabolic and apoptotic signals are large, it is likely that even small lesions will be visible [18]. For these reasons, Tc-labeled annexin A5, a SPECT tracer as a marker of ongoing apoptotic cell death, and 18 F-FDG, a PET tracer as a marker of inflammation, are being evaluated for detecting vulnerable atherosclerotic plaques [18][19][20][21][22][23]. It…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the F(abЈ) fragments of monoclonal IgM antibody Z2D3, which was initially developed with specificity for an antigen expressed by proliferating SMCs of human atherosclerotic lesions, have demonstrated rapid accumulation and good localization of lesions in an experimental atherosclerotic model (28 -29). Fluorine-18-labeled fluorodeoxyglucose has also been used for imaging of carotid artery plaque (30)(31).…”
mentioning
confidence: 99%